Analisis Faktor-Faktor yang Berhubungan dengan Kejadian Stunting di Dinas kesehatan Kabupaten Lahat Tahun 2021 - Rheni Yunita Rahmaniar (Jurnal Kesehatan Saelmakers PERDANA, 2022)
Stunting is a broad indicator to measure the nutritional status of children under five which causes children to experience linear growth retardation. Knowing the factors associated with stunting incidence in the health office of lahat regency in 2021. Cross sectional research design, the population in this study was children under five in Gunung Kembang Village 72 respondents and Prabu Menang Village 57 respondents. The sampling method is purposive sampling technique. The subjects of this study were determined by purposive sampling, namely parents of children and toddlers totaling 129 respondents. This research was conducted in June 2021. The data collection used a questionnaire. The results of the statistical analysis of respondents using the Chi-Square test showed that there was a significant relationship (p‹0.05) for the variables of birth weight and history of exclusive breastfeeding. From this research it was concluded that the Puskesmas should improve programs related to early prevention efforts in children under five, making a class of pregnancy women and giving more information and education about the importance of nutrition during pregnancy and exclusive breastfeeding so that there are no more stunting cases in the working area of ??the Puskesmas.